A motivação das decisões judiciais na perspectiva do processo justo - Lucas Eduardo de Pádua Simões Sena (2021)
This thesis analyzed the duty to motivate court decisions in the Brazilian legal system, from the “due process of law” perspective. The aim was to understand, at a satisfactory level, this requirement scope imposed on the institutional agencies that compose the national Judiciary Power. Therefore, the Michele Taruffo research works were revisited, to consolidate the knowledge of the institute essential elements and characteristics. Since a legal phenomenon can only be properly understood if contextualized within the normative system in which it must operate, the inclusion of the requirement to motivate court decisions from the "due process of law” perspective was carried out. Finally, were addressed the vices that can be committed in court decisions, as well as their legal nature and procedural mechanisms for its correction.